1988
DOI: 10.1021/ic00282a007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of nickelocene. A reinvestigation using inelastic neutron scattering and magnetic susceptibility

Abstract: The magnetic properties of nickelocene, undiluted and doped into ruthenocene and ferrocene, have been determined by susceptibility measurements on powder samples and crystallites oriented in high magnetic fields, respectively, between 4.4 and about 200 K. The results reveal that there is a predominantly ferromagnetic coupling of a nickelocene molecule to its nearest neighbors in an undiluted sample, whereas the interaction with triplet-state molecules at greater distances in diluted samples seems to be antifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 4 publications
4
39
0
Order By: Relevance
“…As for the effect of g-factor anisotropy, this would introduce errors via both the pseudocontact shift and the anisotropy of the contact shift (26,27). The axial and equatorial g-factor components, g || and g ⊥ , of solid nickelocene are 2.0023 and 2.11, respectively (29). This corresponds to a gfactor anisotropy of 5% and justifies the estimation of ρ p from the shift tensor anisotropy.…”
Section: Tensor Analysismentioning
confidence: 66%
“…As for the effect of g-factor anisotropy, this would introduce errors via both the pseudocontact shift and the anisotropy of the contact shift (26,27). The axial and equatorial g-factor components, g || and g ⊥ , of solid nickelocene are 2.0023 and 2.11, respectively (29). This corresponds to a gfactor anisotropy of 5% and justifies the estimation of ρ p from the shift tensor anisotropy.…”
Section: Tensor Analysismentioning
confidence: 66%
“…¼ 2:07. The D value is among the highest observed for discrete nickel(II) complexes [13][14][15][16]. Since g = is lower than g ?…”
Section: Resultsmentioning
confidence: 90%
“…ENDOR measurements on single-doped ruthenocene showed that it incorporates V(bz)2 isomorphically [32]. This was also found for Ni(cp) 2 guest molecules [6].…”
Section: Crystallographically and Magnetically Oriented Probesmentioning
confidence: 53%
“…As we will demonstrate, DT pairs involving a nickelocene triplet are favourable systems to derive exchange parameters from E.P.R. : the triplet ground state of Ni(cp) 2 is split by 33"6cm -1 [6] due to spin-orbit and spin-spin interactions.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation